The Practice of Competition Regulation in the International Procurement and State Procurement Administration in Georgia - Khomeriki, Temuri (Caucasus Journal of Social Sciences, 2013)
Under conditions of the emerging economy, together with the mobilization of the state income, it becomes increasingly important to rationalize the expenses. Under the market economy the government has to intervene in the market functioning in order to protect competitive mechanisms that ensure democratic choice. The regulations of the government includes the implementation of state economic policy, as well as addressing the issues that otherwise are impossible to be solved with self-regulating market mechanisms. The function of supervision the competition legislation is shifting to the judiciary and the special regulatory institutions, but the state procurement administration and anti-monopoly regulations still remain the prerogative of the executive body (the government). In the international practice the systems of the international procurement differs from each other, though they have common characteristics mainly regarding the general principles and applied methods. In addition, the level of procurement centralization and the administration quality varies from country to country. Also in each state there is at least one governmental body (in form of an agency, department, office, etc) that regulates and exercises the overall coordination of the procurement policy throughout the country. Generally this very body is responsible for the monitoring state procurement and administrating the signed contracts. In some countries additionally a special governmental office of public provision is made up that carries out the procurement of standard products and services through tenders on the basis of orders placed by state managing bodies and different organizations and then supply appropriate companies. As it turned out, the similar body is to be established in the near future in Georgia. In order to successfully introduce in Georgia the positive experience existing in the international procurement-management practice, it is equally important to have high quality law, also appropriate institutional infrastructure, the support from the authorities. In addition, it is essential to ensure the availability of the information necessary for public monitoring and the professionalism of the parties participating in the procurement process. In Georgia the law regulating the state procurement is mainly harmonized with international standards, though some indirect related legal acts need further refinement. The experience of the international procurement proves that it is equally important to correctly plan the state procurement, as well as correctly organize the procurement procedures and sign fair contracts. In addition, it is important that obligations written in the contracts are fully implemented and public monitoring requires that the accountability system is strictly defined.